AD, Volume 10, n° 1 & 2, 1985 - Full Issue - Journal System (Africa Development, 1985)
CONTENTS Editorial Note C. ATTΑ-MILLS ............................. i Adjustment under Crisis Conditions in Africa: African Monetary Fund Concept W. WAGACHA ............................... 5 Les Fondements Théoriques des Politiques d'Ajustement du FMI dans les Pays Sous-Développés Makhtar DIOUF ............................ 36 The Continuing Crisis of the Tanzania Economy : The Political Economy of Alternative Policy Options. Ajit SINGH ..................................... 51 The Budget and the People Horace CAMPBELL .......................... 72 Crise Economique et Financière — Austérité & FMI: Le Cas du Maroc Habib El MALKI ............................... 90 Programme d'Ajustement Structurel du FMI Najib AKESBI ................................... 101 IMF Adjustment Policies in Ghana since 1966 Eboe HUTCHFUL .............................. 122 Ghana's Stabilization Measures and the IMF: A Case Study Bank of Ghana ..................................137 Les Mesures de Réajustement de l'Economie Ivoirienne face à la Crise Economique Mondiale : Leurs Résultats et leurs Implications Sociales . Bamba MOUSSA ............................150 FMI en Guinée : Un Programme très Contestable Alain COURNANEL ........................... 161 Understanding and Resolving the Current Economic Crisis in Nigeria Yusufa Usman ΒALA ..........................169 A Case Study of Stabilization Measures in Nigeria Akinola A. OWOSEKUN .......................... 208 The Current Austerity Measures and their Impact on the Nigerian Economy J. Ο. ADERIBIGBE .............................. 217 «Home Grown»(?) Austerity Measures: The case of Zimbabwe Thandika MKANDAWIRE ......................... 236 The IMF and the Adjustment of the Colombian Economy to Recession Fernando ROJAS .................................. 264 DOCUMENTS The IMF and World Bank Conditionality: Tanzanian Case Kighoma A. MALIMA ................................ 285 «The Zaria Declaration of African Social Scientists on the Adjustment of the African Economies to the Wodd Economic Crisis» (English and French) .................298